CRYPTOCURRENCY IN ISLAMIC LAW - M. Usman; Uju Suji'ah; Muh. Nashirudin (Jurnal Multidisipliner Bharasa, 2022)
Virtual money is a product of specific cryptocurrency algorithms, where no particular institution or authority controls the circulation of this digital money or underlying assets for which there is no basis for pricing and consumer protection. By ceding the money system into the market, Cryptocurrencies require legality considerations. This research aims to explain cryptocurrency as a means of payment from the perspective of Islamic Law. This research uses a literature review or normative approach. The results showed that a Legal Vacuum or the empty laws governing Cryptocurrencies could potentially negatively impact. This is because there is the principle of haram li ghairihi, where something contains an element of uncertainty. In the Indonesian Ulema Council (MUI) perspective through Fatwa No. 116/DSN/-MUI/IX/2017, cryptocurrency is included in the concept of sharia maqashid due to uncertainty of containing element maysir (gambling).